A Model for Behavioral Consultation in Rural School Districts. (March 2017) - Traub, Michele R.; Joslyn, P. Raymond; Kronfli, Faris R.; Peters, Kerri P.; Vollmer, Timothy R.
The demand for behavioral services is currently outpacing the availability of trained and certified behavior analysts. This need might be felt most acutely in rural communities, where educational funds often do not allow for hiring full-time behavioral staff. This article outlines a model for behavioral consultation that has been successful in several rural school districts. Strategies to build rapport, recommendations for assessment and treatment planning, and methods of expanding the role of the behavior analyst within the school are discussed. Finally, resources for teachers and administrative staff to access behavioral services and pertinent research are included.